(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
The main goal of the research is to develop constructive measures to ensure even distribution of water in the pre-chamber of irrigation system pumping stations and water intake structures, and to improve hydraulic conditions when supplying water to pumps. The authors developed a technical solution that includes an element that affects the movement of water in front of suction pipes. This ensures stable, cavitation-free operation of pumps, prevents expensive and complicated reconstruction of pumping stations, and ensures reliable water supply of pumping stations.